Challenges of Artificial Intelligence and its Impact on the Quality of Internal Auditing and its Impact on the Performance of Financial Institutions. - Sakhil, Amel Merzah; Kadhim, Suhad Abdul Meer; Oudah, Fatimah Flayyih (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The study aims to demonstrate the extent to which the challenges of artificial intelligence technologies affect the quality of internal audit and their impact on the performance of financial institutions. With the growth of applications of artificial intelligence in financial operations, institutions have begun to increasingly rely on automation, intelligent data analysis, and machine learning in carrying out their daily tasks. While these technologies are expected to enhance efficiency and speed, they pose major challenges for internal audit units, including understanding complex systems, difficulty tracking algorithms, The possibility of technical biases or inaccurate automated decisions. The problem of the study is to identify the challenges posed by artificial intelligence technologies to the quality of internal audit, which may directly or indirectly affect the effectiveness and sustainability of the performance of financial institutions, and the extent of the readiness of internal audit units to deal with the smart systems adopted within these institutions and their impact on performance, in (Iraqi Trade Bank, Al-Nahrain Islamic Bank) the study sample, The research was based on a basic hypothesis, that the challenges of artificial intelligence affect the quality of internal audit, which is reflected in the performance of financial institutions. The research reached a number of conclusions, the most important of which are: Artificial intelligence technologies contribute to improving the quality and efficiency of internal audit by adapting to smart systems and understanding complex systems, which is reflected positively on the performance of financial institutions The research recommended the need to train auditors on the use of artificial intelligence tools and encourage institutions to replace manual systems with computerized systems to improve oversight performance and enhance cooperation between information technology and internal audit teams to ensure effective integration that ensures the quality of internal audit, which is reflected in improved performance.